Identification of key miRNAs as regulatory biomarkers of gonadotropins leading to infertility in males - N. A. Oohayyed; M. M. Mohammed; A. M. Al-Rahim; R. N. Al Chalabi; S. A. Shaban; A. A. J. Suleiman (IRBIS LLC, 2023)
Introduction. Infertility is a highly fatal reproductive system disorder that affects the ability of a couple to reproduce. Over the past decades, a drastic uplift has been recorded in infertility cases among males ranging from 20 to 70 % indicating spermatogenesis impairment.Aim: to identify key microRNAs (miRNAs) as regulatory biomarkers of gonadotropins involved in dysregulation of fertility-related genes to propose potential therapeutic strategies that would combat the action of oncogenic miRNAs (oncomiRs).Materials and Methods. Interaction analysis was performed between miRNAs and fertility-related genes namely luteinizing hormone choriogonadotropin receptor (LHCGR), gonadotropin-releasing hormone receptor (GnRHR), follicle-stimulating hormone receptor (FSHR) and cystic fibrosis transmembrane conductance regulator (CFTR) to identify key miRNAs as regulatory biomarkers of gonadotropins leading to infertility in males.Results. A total of 10, 13, 31 and 18 strong and potential binding sites were predicted for miRNAs-LHCGR, miRNAs-GnRHR, miRNAs-FSHR, and miRNAs-CFTR respectively employing miRWalk (comprehensive genetic database including miRNA targets) followed by identification of 6, 18, 55 and 17 significant interactions through RNA22. Subsequently shortlisted miRNAs and messenger RNA (mRNA) regions were subjected to Vfold-Pipeline and RNAComposer individually for 3D structure prediction. Additionally molecular docking was carried out between miRNAs and mRNAs models that discovered potential and stable interactions elucidating miR-6880-FSHR(R2) as a highly stable complex with least binding affinity (-566.3) and high confidence score (0.999).Conclusion. Hence this study proposes key oncomiRs as a diagnostic biomarker and therapeutic target to bring about a promising treatment strategy against male factor infertility. However wet lab investigations are required for further validations of proposed study.